Decision Support System for Determining the Quantity of Brick Production Using the Fuzzy Tsukamoto Method - Nurpa, Murni Zaliah; Masrizal, Masrizal; Nasution, Marnis (Forum Kerjasama Pendidikan Tinggi, 2024)
Maximum profits are obtained from maximum sales. Maximum sales are those that can meet existing demands. There is a determination of the planned production amount to meet production levels to meet planned sales levels or market demand levels. Factors that need to be considered in determining production quantities include: the amount of inventory and the amount of demand. The amount of demand and supply is an uncertainty. Fuzzy logic is a science that can analyze uncertainty. One of the fuzzy rule methods is Tsukamoto, which is a method that is often used to build a system whose reasoning resembles human intuition or feelings. The calculation process is quite complex so it takes a relatively long time, but this method provides results with quite high accuracy. Ratu Batubata Refinery is a factory that produces large quantities every day. Therefore, planning the amount of brick production is very important. In order to meet market demand appropriately and in appropriate quantities. By using this application, it is hoped that the company can make it easy for the company to predict production quantities based on the amount of demand and existing inventory data, in order to achieve maximum profits.